Consistency in Accounting Policies and Financial Statement Comparability (gjstudies, 2017)
This research introduces a novel, cross-disciplinary methodology for quantifying the impact of accounting policy consistency on financial statement comparability, a long-standingbut qualitatively assessed concept in accounting theory. Departing from traditional archivalor survey-based approaches, we develop a computational linguistics and network analysisframework to model the accounting policy ecosystem of firms. We conceptualize accounting policies not as isolated choices but as interconnected nodes within a firm-specific andindustry-wide semantic network. By parsing the accounting policy disclosures from a comprehensive dataset of 10-K filings from 1995 to 2004, we construct policy adjacency matricesand measure inter-firm policy network similarity. Our primary innovation is the Policy Consistency and Comparability Index (PCCI), a multi-dimensional metric that captures thestability of a firm’s policy network over time (consistency) and its topological alignmentwith peer firms’ networks (comparability). Results from applying this framework to theSP 500 constituent firms reveal a non-linear, threshold-based relationship between policyconsistency and market-based measures of information asymmetry, such as bid-ask spreadsand analyst forecast dispersion. We find that high levels of internally consistent policy application, when coupled with high external comparability, are associated with a significantreduction in cost of capital estimates. Conversely, we identify a ’consistency trap’ where rigidadherence to a unique, non-comparable set of policies can diminish informational value. Thisstudy’s primary contribution is the formalization and computational operationalization ofpolicy consistency-comparability nexus, providing auditors, regulators, and investors with aquantitative diagnostic tool. The findings challenge the implicit assumption that more consistency is invariably beneficial, highlighting instead the critical interplay between internalcoherence and external alignment in the financial reporting ecosystem.